ANALISIS HUBUNGAN RELIGIUSITAS, POLA ASUH KELURGA, DAN TEMAN SEBAYA DENGAN STATUS PENYALAHAGUNAAN NAPZA PADA REMAJA DI WILAYAH KECAMATAN PRAYA TIMUR KABUPATEN LOMBOK TENGAH TAHUN 2019 - Iwan Wahyudi; Toha Muahimin; Syamsul Anwar; Muhammad Amrullah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Drug stands for Narcotics, Psychotropic, and other addictive substances. The aim of this study was to analyze the relationship between religiosity, parenting family and peers with drug abuse in adolescents in the Praya Timur District, Central Lombok Regency, West Nusa Tenggara Province. The study conducted was descriptive correlation with cross sectional approach in 324 adolescents. Data analysis using bivariate analysis using Chi-square The results of religiosity analysis (p value = 0,000), family upbringing (p value = 0.004) and peers (p value = 0,000) were significantly associated with drug abuse status in adolescents with p value < 0.05. While gender (p value = 0.000), and age (p value = 0,004) are related to drug abuse status and are variable confounding. Education (p value = 0.731) and socio-economic (p value = 0.125) are not related to the misuse of drugs with a p value> 0.05. The results of this study have the greatest influence on the development of drug abuse in adolescents, namely religiosity with p value 0.000 with OR 6.243 Based on the results of this study, it is necessary to make efforts for community and government nurses to prevent an increase in drug abuse cases by taking into account aspects or factors that have a major influence on drug abuse.